ISLAM DAN SINKRETISME DI JAWA - Masyhudi (BRIN, 2003)
The strategy adopted by Islamic propagators in the northern coastal areas of Java is different from the strategy applied in several areas in the interior of Java. Their trading strategy is the dominant step, besides being carried out by education, marriage and adopting local arts with loads included with Islamic contents. However, in the following period the dominant strategy adopted by Islamic propagation figures in several hinterland areas of Java was through education with institutions such as Islamic boarding schools and tarekat organizations which were the actualization of the teachings of Sufism. However, there has been a syncretization process that focuses on the cognitive and behavioral aspects of Javanese society, as a result of the existence of two cultures (pre-Islamic and Islamic) that touch each other, then they are processed in such a way that there is no conflict. And in the end Islam was accepted by most Javanese people.